2007
DOI: 10.1073/pnas.0703178104
|View full text |Cite
|
Sign up to set email alerts
|

Scm3, an essential Saccharomyces cerevisiae centromere protein required for G 2 /M progression and Cse4 localization

Abstract: A universal mark of centromeric chromatin is its packaging by a variant of histone H3 known as centromeric H3 (CenH3). The mechanism by which CenH3s are incorporated specifically into centromere DNA or the specialized function they serve there is not known. In a genetic approach to identify factors involved in CenH3 deposition, we screened for dosage suppressors of a temperaturesensitive cse4 allele in Saccharomyces cerevisiae (Cse4 is the S. cerevisiae CenH3). Independent screens yielded ORF YDL139C, which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
163
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(171 citation statements)
references
References 45 publications
7
163
1
Order By: Relevance
“…CenH3, the centromeric version of H3, is perhaps the most enigmatic histone variant in that it may form non-canonical nucleosomes. Three independent studies (mostly based on in vivo experiments) have shown that yeast CenH3 (Cse4) forms a centromere-specific nucleosome together with H4 and the non-histone protein Scm3 [19] [20] [21]. In fact, it has been suggested that Scm3 may be a Cse4-specific histone chaperone [21].…”
Section: H3 Variantsmentioning
confidence: 99%
See 2 more Smart Citations
“…CenH3, the centromeric version of H3, is perhaps the most enigmatic histone variant in that it may form non-canonical nucleosomes. Three independent studies (mostly based on in vivo experiments) have shown that yeast CenH3 (Cse4) forms a centromere-specific nucleosome together with H4 and the non-histone protein Scm3 [19] [20] [21]. In fact, it has been suggested that Scm3 may be a Cse4-specific histone chaperone [21].…”
Section: H3 Variantsmentioning
confidence: 99%
“…Three independent studies (mostly based on in vivo experiments) have shown that yeast CenH3 (Cse4) forms a centromere-specific nucleosome together with H4 and the non-histone protein Scm3 [19] [20] [21]. In fact, it has been suggested that Scm3 may be a Cse4-specific histone chaperone [21]. There is also evidence (mainly from in vivo protein -protein crosslinking) that cenH3 containing nucleosomes in Drosophila cell lines can exist as 'hemisomes', that is, that they consist of only one copy each of cenH3, H4, H2A, and H2B [22].…”
Section: H3 Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is distantly related to the yeast centromeric protein Scm3 (Camahort et al 2007;Mizuguchi et al 2007;Stoler et al 2007;Sanchez-Pulido et al 2009). HJURP interacts directly with CENP-A and histone H4, localizes CENP-A to the centromere in a cell cycle-dependent manner, and enables the deposition of newly synthesized CENP-A into the centromeric nucleosome.…”
mentioning
confidence: 99%
“…CENP-A, as a specialized histone, has a specialized chaperone known as HJURP in humans or Scm3 in yeast. S. cerevisae Scm3 was identified in immunopurifications of CENP-A Cse4 and is required to target CENP-A Cse4 to centromeres (Camahort et al 2007;Mizuguchi et al 2007;Stoler et al 2007). Scm3 can assemble CENP-A Cse4 into nucleosomes in vitro (Shivaraju et al 2011).…”
Section: Hjurp: the Cenp-a Chaperonementioning
confidence: 99%